Antioxidant, anti-inflammatory and anticancer activities of methanolic extracts from Jatropha curcas Linn. - Oskoueian, Ehsan; Abdullah, Norhani; Saad, Wan Zuhainis; Omar, Abdul Rahman; Ahmad, Syahida; Kuan, Wen Bin; Zolkifli, Nor Azlina; Hendra, Rudi; Ho, Yin Wan (Academic Journals, 2011)
A comprehensive study on the phytochemical contents and biological activities of the methanolic extract from different parts of Jatropha curcas Linn. was conducted. The extracts of different plant parts contained various levels of phenolics, flavonoids and saponins. Latex and leaf extracts showed the highest antioxidant activity. Root and latex extracts inhibited the inducible nitric oxide synthase in macrophages RAW 264.7, comparable to L-Nitro-Arginine Methyl Ester (L-NAME), indicating appreciable anti-inflammatory activities. Cytotoxicity assay results indicated the anticancer therapeutic property of the root extract against human colon adenocarcinoma (HT-29) cell line but its cytotoxic effect on human hepatocyte (Chang cell) was high.